Glycyrrhiza Glabra L. - Technology of Cultivation of Medicinal Plants (Texas Journal of Agriculture and Biological Sciences, 2023)
The article focuses on the medicinal properties of the plant, its use for diseases, and the technology of cultivation from seeds and cuttings of the plant. When the plant was planted from seed, the row spacing was 60x10, 60x20, 60x30 sm